2014
DOI: 10.1002/cbic.201400002
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Thioether Crosslinking of Therapeutic Proteins to Increase Proteolytic Stability

Abstract: Protein-based pharmaceuticals typically display high selectivity and low toxicity, but are also characterized by low oral availability, mainly because of enzymatic degradation in the gastrointestinal tract and poor permeability across the intestinal wall. One way to increase the proteolytic stability of peptides and proteins is by intramolecular crosslinking, such as the introduction of disulfide bridges. However, disulfide bridges are at risk of thiol-disulfide exchange or reduction during production, purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Through the use of the chemical crosslinking strategy presented here the substitution of the amino acid residues that potentially are part of the binding site is avoided, and, as shown by the CD and SPR experiments, the intramolecular crosslinks do not affect the conformation of the protein domain or interfere with the binding. Together with our earlier results on stabilization of an albumin‐binding domain, this study shows that intramolecular chemical crosslinking can be used to increase the stability of small, helical proteins towards gastrointestinal proteases without negatively affecting their function. Even an oral bioavailability as low as 1 % has been shown to result in oral activity for biologically active peptides, and so we envision that the presented strategy could be a step towards orally available protein drugs.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Through the use of the chemical crosslinking strategy presented here the substitution of the amino acid residues that potentially are part of the binding site is avoided, and, as shown by the CD and SPR experiments, the intramolecular crosslinks do not affect the conformation of the protein domain or interfere with the binding. Together with our earlier results on stabilization of an albumin‐binding domain, this study shows that intramolecular chemical crosslinking can be used to increase the stability of small, helical proteins towards gastrointestinal proteases without negatively affecting their function. Even an oral bioavailability as low as 1 % has been shown to result in oral activity for biologically active peptides, and so we envision that the presented strategy could be a step towards orally available protein drugs.…”
Section: Resultssupporting
confidence: 82%
“…However, the discrepant shape of the melting curves suggests that the unfolding of the K58 and K4K58 variants is a gradual transition rather than a cooperative two‐state transition. This result was not unexpected, because we had previously observed that intramolecular crosslinking of a different three‐helix protein resulted in variants that showed non‐cooperative unfolding in variable‐temperature measurements, making it impossible to determine a melting temperature reliably …”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, the similar result for the C91S mutant excludes this possibility since an internal disulfide could not occur with the mutant protein. An alternative possibility to account for the observed mass of Prdx6 is the loss of 2 H + resulting in the formation of a thioether, but that appears to be relatively rare in non-engineered proteins and a mechanism for its possible formation is not clear (30). The most likely possibility for the observed molecular mass of non-reduced Prdx6 is the auto-oxidation of Prdx6 to the sulfenic acid (-Cys S-OH) and its subsequent dehydration with formation of a sulfenylamide bond between the sulfur atom of C47 and the nitrogen of an adjacent amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…Our mass spectroscopic evaluation of the recombinant protein following storage (that presumably was accompanied by auto-oxidation of the protein) indicated a molecular mass that was 2 Da less than the predicted mass of the reduced protein [35]. Based on this finding, we have proposed that a sulfenylamide forms through dehydration of oxidized Prdx6 (reduced protein +16 for “O” −18 for H 2 O =−2) [35]; an alternative possibility for the measured mass is a thioether, but that is extremely rare in nature [67]. As noted in the review by Forman in this volume, sulfenylamide formation of a protein in vivo requires the reactivity of its sulfhydryl group toward peroxides that is in the range demonstrated by Prdx6.…”
Section: Enzymatic Activites Of Prdx6mentioning
confidence: 99%